Emerging challenges in aquaculture: Current perspectives and human health implications - M. Oghenebrorhie Ruben; A. Bolanle Akinsanola; M. Ekemini Okon; Teslim Shitu; I. Iretomiwa Jagunna (Veterinary World)
Aquaculture, the cultivation of aquatic organisms for human consumption, has become an essential contributor to global food security. However, it faces numerous challenges that threaten its sustainability and capacity to meet the growing demand for animal protein. This review investigates these challenges, with a particular focus on environmental degradation, public health risks, and ethical dilemmas posed by genetic interventions in fish breeding. Despite the promise of genetically modified organisms (GMOs) in enhancing fish production, their integration into aquaculture remains controversial due to potential risks and unresolved ethical questions. This study aims to provide a comprehensive understanding of these pressing issues and propose pathways for sustainable aquaculture development. With the global population increasing and the demand for animal protein intensifying, aquaculture holds great potential as a sustainable food source. However, its contribution to global protein demand remains minimal, projected to decline to as low as 4% in the coming decades. Furthermore, aquaculture’s environmental impact, including pollution of water bodies and ecosystem disruption, poses serious threats to biodiversity and public health. Addressing these challenges is critical for ensuring the long-term viability of aquaculture. By exploring the intersection of sustainability, ethics, and innovation, this review provides valuable insights for policymakers, industry stakeholders, and researchers seeking to advance sustainable aquaculture practices. This study aims to evaluate the current state of aquaculture and identify key challenges related to environmental sustainability, public health, and ethical considerations. It seeks to explore the potential of sustainable practices and genetic interventions to address these challenges while balancing the need for increased production and societal acceptance. The ultimate goal is to offer practical recommendations for fostering a resilient and ethical aquaculture industry capable of meeting future global food demands.